Evaluation of Sargassum sp. as a nutrient-sink in an integrated seaweed-prawn (ISP) culture system - Mai, H.; Fotedar, Ravi; Fewtrell, Jane (Elsevier BV, 2010)
Effluent water from intensive prawn aquaculture systems typically has a high concentration of dissolved nutrients such as nitrogen and phosphorus. A study was conducted for 42 days to investigate the nutrient flow in a system where brown seaweed (Sargassum sp.) was integrated into western king prawn (Penaeus latisulcatus) culture. Three treatments namely, western king prawn monoculture (5.48 ± 0.29 g), Sargassum sp. monoculture and seaweed/prawn integrated culture were tested for nutrient flow among feed, water and species cultured. The results showed that by integrating seaweed into prawn culture, the concentrations of total ammonium nitrogen (TAN), nitrite–nitrogen (NO2−) and nitrate–nitrogen (NO3−), dissolved inorganic nitrogen (DIN), total nitrogen (TN), phosphate (PO43−) and total phosphorus (TP) were significantly lower (p < 0.05) in the integrated culture system than in the prawn monoculture (p < 0.05) and remained within non-toxic limits for the duration of the study.In addition, the integration of Sargassum sp. with western king prawn culture did not significantly alter the nitrogen and phosphorus conversion rates from feed into prawns (approximately 17.69–18.99 and 13.79–14.47%, respectively). The specific growth rate (SGR) and survival rate of the prawns in integrated treatment did not significantly differ (p > 0.05) from the prawn monoculture. The mean biomass of Sargassum sp. in integrated culture increased at the rate of 3.16 ± 0.74% g day−1 after 7 days of the study, which was significantly higher than in the monoculture system (5.70 ± 0.82% g day−1). The results suggest that integrating Sargassum sp. into western king prawn culture can benefit prawn farming by assisting in the maintenance of optimum water quality and thereby, reducing environmental impacts on surrounding areas.